2020
DOI: 10.1038/s41598-020-64916-2
|View full text |Cite
|
Sign up to set email alerts
|

Leuconostoc mesenteroides fermentation produces butyric acid and mediates Ffar2 to regulate blood glucose and insulin in type 1 diabetic mice

Abstract: Type 1 diabetic patients have lower counts of butyric acid-producing bacteria in the dysbiotic gut microbiome. In this study, we demonstrate that a butyric acid-producing Leuconostoc mesenteroides (L. mesenteroides) EH-1 strain isolated from Mongolian curd cheese can reduce blood glucose and IL-6 in the type 1 diabetic mouse model. L. mesenteroides EH-1 fermentation yielded high concentrations of butyric acid both in vitro and in vivo. Butyric acid or L. mesenteroides EH-1 increased the amounts of insulin in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 66 publications
1
36
0
1
Order By: Relevance
“…When comparisons were made across L. mesenteroides and other isolates, the lowest Ca 2+ ions was release by L. mesenteroides . The results of high acid production but low tooth demineralization could be explained by the fact that some type of L. mesenteroides strain produce butyric acid instead of lactic acid, since there is lack of evidence to confirm the association between butyric acid and dental caries [ 46 ]. These results suggested that acid production and acid resistance alone could not determine the cariogenicity of a bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…When comparisons were made across L. mesenteroides and other isolates, the lowest Ca 2+ ions was release by L. mesenteroides . The results of high acid production but low tooth demineralization could be explained by the fact that some type of L. mesenteroides strain produce butyric acid instead of lactic acid, since there is lack of evidence to confirm the association between butyric acid and dental caries [ 46 ]. These results suggested that acid production and acid resistance alone could not determine the cariogenicity of a bacterium.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous phase was transferred to an autosampler vial and 100 μL of concentrated HCl were added. The analysis of butyric acid was performed using an Agilent 1200 series HPLC system with a ZORBAX Eclipse XDB-C18 column (4.6 × 250 mm, 5 μm) [ 16 ]. The mobile phase consisted of 20 mmol/L NaH 2 PO 4 solution (pH 2.2) and acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were fasted for 4-8 h on the last day of treatment. The level of blood glucose from the tail blood was measured using a glucometer [16]. The abdominal fat mass was photographed and weighted.…”
Section: Feeding Mice With L Mesenteroides Eh-1 and Ffar2 Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations